Holism in Ancient Medicine and its Reception - Thumiger, Chiara, (Studies in Ancient Medicine ;, 2021)
This volume aims at exploring the ancient roots of 'holistic' approaches in the specific field of medicine and the life sciences, without, however, overlooking the larger theoretical implications of these discussions. Therefore, the project plans to broaden the perspective to include larger cultural discussions and, in a comparative spirit, reach out to some examples from non Graeco-Roman medical cultures. As such, it constitutes a fundamental contribution to history of medicine, philosophy of medicine, cultural studies, and ancient studies more broadly. The wide-ranging selection of chapters offers a comprehensive view of an exciting new field: the interrogation of ancient sources in the light of modern concepts in philosophy of medicine, as justification of the claim for their enduring relevance as object of study and, at the same time, as means to a more adequate contextualisation of modern debates within a long historical process.